Penerapan Artificial Intelligence (AI) untuk Meningkatkan Efisiensi Operasional di Perusahaan Manufaktur: Studi Kasus PT. XYZ - Novita, Yenni; Zahra, Rita (Jurnal Manajemen dan Teknologi, 2024)
The application of Artificial Intelligence (AI) has become a major focus in increasing operational efficiency in various industrial sectors, including manufacturing. This research explores the application of AI in improving operational efficiency at PT. XYZ, a manufacturing company operating in a certain sector. Using a qualitative approach with case studies as the main framework, this research collects data through interviews with company management, observations on the production floor, and historical data analysis. Research findings show that AI implementation has had a positive impact by improving productivity, product quality and supply chain management. However, challenges such as limited skilled human resources and high implementation costs were also identified. Based on the findings, suggestions were put forward, including investment in employee training, implementation cost reduction strategies, exploration of broader AI integration, and increased awareness of the benefits of AI among employees and stakeholders. By implementing these suggestions, PT. XYZ can further maximize the potential of AI to increase operational efficiency and maintain its competitiveness in the manufacturing industry. This research also makes an important contribution to manufacturing industry stakeholders more broadly and to the academic literature on AI and the manufacturing industry.